Relacionamento interorganizacional e suas influências sobre as organizações participantes da rede de regimes próprios de previdência social - Lopes, Celso Egidio (2011)
The object of this research is to identify, through a case study, the infuence of the interorganizational relationship on the organizations participating in a specific network Social Security Systems, located in the Metropolitan Region of Curitiba. The level of analysis considered was the network and the organizations were analyzed as units. Primary data were collected through semi-structured interviews, structured questionnaires and observation at meetings and events. Secondary data were collected from the informative, the legislation, internet sites and newspapers. The sample consisted of at least one head of each organization researched in the network. Directing superior levels leaders and strategic level ones were interviewed. Thus, the sample tested is represented by the RPPS group plus APEPREV one. Together the organizations cited as "organizations considered in decision-making" by the researcher and the organizations that comprise the sample, the network under study consists of 45 (forty five) organizations. The research is exploratory and descriptive with qualitative and quantitative approach. The Researcher used the analysis of narrative, descriptive and qualitative analysis, documentary analysis and technical analysis of social network also known as Social Network Analysis (SNA). Concerning to the expected results of a network, the highlights were the learning activities, the institutional, trust and transfer of information. The institutional entrepreneurship was present in the research through the formation of new arrangements, processes of de-institutionalization, organizational learning and knowledge production between the network actors.